Biaya Kepatuhan dan tarif Pajak Terhadap Penggelapan Pajak - Jaendry, Gregorius (Insan Cita Bongaya Research Journal, 2022)
Abstract: This study aimed to examine the effect of Compliance costs and tax rate on tax evasion with self assessment system and tax moral As Moderation Variabel. The population in this study is the individual taxpayers list in KPP Pratama Ternate City many as 84.271 with sample of 95 respondent. The samples were taken using convenience sampling The samples were taken using method. Methods of data collection is a survey method using Questionnaire. The results of this study indicate that Compliance costs and tax rate effect on tax evasion, self assessment system moderate the relationship between Compliance costs and tax rate effect on tax evasion, tax moral unable to moderate the relationship between Compliance costs and tax rate effect on tax evasion. Keywords: Compliance costs, tax rate, self assessment system, tax moral and tax evasion